การพัฒนาการจัดการเรียนรู้โดยใช้กระบวนการโพลยาร่วมกับเทคนิคบาร์โมเดล เพื่อส่งเสริมทักษะการแก้โจทย์ปัญหาเรื่อง การบวกและการลบเศษส่วน สำหรับนักเรียนชั้นประถมศึกษาปีที่ 4 - ยั่งยืน, นภสร; ปาณาวงษ์, ชำนาญ (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2020)
บทคัดย่อ การวิจัยนี้มีวัตถุประสงค์เพื่อพัฒนาการจัดการเรียนรู้โดยใช้กระบวนการโพลยาร่วมกับเทคนิคบาร์โมเดล เพื่อส่งเสริมทักษะการแก้โจทย์ปัญหา เรื่อง การบวกและการลบเศษส่วน สำหรับนักเรียนชั้นประถมศึกษาปีที่ 4 ดำเนินการโดยใช้กระบวนการวิจัยและพัฒนาดังนี้ ขั้นที่ 1 สร้างและหาประสิทธิภาพการจัดการเรียนรู้ ให้มีประสิทธิภาพตามเกณฑ์ 75/75 โดยทดลองใช้กับนักเรียน 3 คน เพื่อตรวจสอบด้านภาษา เนื้อหา และด้านเวลา หลังจากนั้นทดลองใช้กับนักเรียน จำนวน 9 คน และ 19 คน เพื่อหาประสิทธิภาพการจัดการเรียนรู้ ขั้นที่ 2 ศึกษาผลการจัดการเรียนรู้ระหว่างก่อนและหลังเรียน หลังเรียนกับเกณฑ์ ร้อยละ 75 และศึกษาพฤติกรรมการแก้โจทย์ปัญหาของนักเรียนระหว่างการจัดการเรียนรู้ ขั้นที่ 3 ศึกษาความพึงพอใจของนักเรียนหลังต่อการจัดการเรียนรู้ ผลการวิจัยพบว่า 1. ผลการสร้างการจัดการเรียนรู้โดยใช้กระบวนการโพลยาร่วมกับเทคนิคบาร์โมเดล จำนวน 4 แผน มีความเหมาะสมอยู่ในระดับมาก ( = 4.09, S.D. = 0.33) มีประสิทธิภาพเท่ากับ 72.81/75.26 ซึ่งเป็นไปตามเกณฑ์ 75/75 2. นักเรียนที่เรียนด้วยการจัดการเรียนรู้โดยใช้กระบวนการโพลยาร่วมกับเทคนิคบาร์โมเดล เกิดทักษะการแก้โจทย์ปัญหา หลังเรียนสูงกว่าก่อนเรียน และสูงกว่าเกณฑ์ร้อยละ 75 อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 3. นักเรียนมีความพึงพอใจต่อการจัดการเรียนรู้โดยใช้กระบวนการโพลยาร่วมกับเทคนิคบาร์โมเดล อยู่ในระดับมากที่สุด ( = 4.65, S.D. = 0.90) คำสำคัญ : กระบวนการโพลยา เทคนิคบาร์โมเดล ทักษะการแก้โจทย์ปัญหา ABSTRACT The objectives of this research is to development learning activities by Polyas processes co-operating with Bar Model to promote problem solving skills about the problem of addition and subtraction of fractions for Prathomsuksa 4 students. The proceed by using the research and development process as follows, Step one: create and find out the efficiency of learning activities with the efficiency value of 75/75. Tested with 3 students for investigating the appropriate of language, content and time spending on learning activity, after that tested with 9 and 19 students for finding out efficiency of learning activity. Step two: study the result of learning activities to between before and after learning and compare result of after learning with criterion is 75 percent and to study the problem solving behaviors of students during the learning management. Step three: To study the satisfaction of students after learning activities. The findings of the study indicated that: 1.The result of learning activities by Polyas processes co-operate with bar model is 4 plan was in high levels (mean = 4.09, S.D. = 0.33) and the efficiency was 72.81/75.26 with the efficiency value of 75/75 2. The students learned activity by using Polyas process co-operate with bar model had problem solving skill after learning higher than before learning and higher than 75 percent with statistical significance at the level of .05 3. Students are satisfied with learning activities by Polyas processes co-operate with bar model was in highest levels (mean = 4.65, S.D. = 0.90) Keywords: Polyas Processes, Bar Model, Problem Solving Skills